Epistemologi Islam dalam Perspektif Ontologis dan Aksiologis - Lilia Afriani; Uswatun Hasanah (Medan Resource Center, 2026)
Epistemology, commonly understood as the theory of knowledge, occupies a central position in Islamic intellectual tradition, where human reason and sensory perception are acknowledged as legitimate means of acquiring knowledge, albeit within inherent limitations. This article aims to examine Islamic epistemology through an integrated ontological and axiological perspective, focusing on how sources of knowledge are conceptualized and function within Islamic philosophy. Employing a philosophical-analytical approach, the study explores the structural frameworks of Islamic epistemology—namely bayani, irfani, and burhani—and situates them within broader discussions of ontology and axiology. The findings demonstrate that Islamic epistemology does not treat revelation, reason, and empirical experience as competing sources, but as complementary foundations of knowledge. Ontologically, Islamic thought positions God as the ultimate source of value, while humans function as moral agents entrusted with stewardship grounded in the principle of tawhid. Axiologically, knowledge is viewed as inherently value-laden, serving ethical, spiritual, and civilizational purposes. This study argues that such an integrated epistemological framework enables Islamic thought to bridge moral values and modern scientific inquiry while contributing to the formation of a holistic conception of human knowledge.